Bank Sampah Sebagai Alternatif Penyelesaian Sampah Yang Berkelanjutan Dan Peningkatan Ekonomi Di Desa Jatiwangsan Kecamatan Kemiri Kabupaten Purworejo - Yuli Widiyono; Arif Susanto; Ari Fajar Isbakhi; Nurholis Nurholis; Citra Maharani Ivoniya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Garbage Bank program carried out in Jatwansan village, Kemiri sub-district, Purworejo district, Central Java is in the form of workshop activities attended by the local Jatiwangsan Village community. This activity workshop